IMPLEMENTASI HUKUM ISLAM DALAM PEMIKIRAN MU’TAZILAH - Muliati Muliati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: In modern times and the advancement of science and technology, the rational Mutazilah teachings have begun to re-emerge among Muslims especially among the intelectual counity. Unknowingly they have had the same or close understandings of the Mutazila teachings. Having such ideals does not exclude them from Islam.